Risk, Responsibility, and Regulation: A Socio-Legal Analysis of Notarial Accountability in Identifying Beneficial Ownership - Aljula, Muhammad Yusron; Hartanto, Hartanto (Baileo: Jurnal Sosial Humaniora, 2025)
This paper aims to analyze the legal accountability of notaries in fulfilling their obligation to identify the Beneficial Ownership, as mandated by Presidential Regulation No. 13 of 2018 on the Implementation of the Principle of Knowing the Beneficial Owner of Corporations. Employing a normative juridical approach and comparative legal method, this study examines the scope of notarial liability and the extent of legal protection afforded through the Beneficial Ownership Declaration Letter. Findings highlight the strategic role of notaries as gatekeepers in preventing money laundering and terrorism financing, particularly through their authority to identify parties and inquire into corporate beneficial ownership. However, this responsibility carries the risk of legal overburden if not supported by adequate legal safeguards. While the Declaration Letter may serve as evidence of due diligence, its probative value is only conclusive if uncontested. Thus, regulatory reform is needed to clarify that notarial responsibility is limited to formal truth based on client declarations, not material truth. The novelty of this study lies in its socio-legal argument for reconstructing norms of notarial liability amid an increasingly complex anti-money laundering regime. The main recommendation calls for harmonizing the identification duty with the statutory limits of notarial authority to balance legal risk, responsibility, and protection.